Analysis of forced convection of Nanofluid over stretching sheet with suction effect - ., pragya; R. Vasanthakumari, Dr. (International Journal of Engineering and Technology, 2019)
The present paper analyses boundary layer flow of incompressible nanofluid with MHD along stretching sheet with forced convection. This problem is of great practical utility. Similarity transformation has been used and PDE are converted into ODE. Equations are then solved using HAM (Homotomy Analysis Method). Many parameters are investigated and results are depicted with the help of graphs. Skin friction coefficient and rate of heat transfer are shown with the help of graphs and tables.Â